DEVELOPING INTERACTIVE LEARNING MEDIA ON TRIGONOMETRY SUBJECT FOR STUDENTS IN GRADE X - Rinda Hidayanti; Suparman Suparman (Universitas Ahmad Dahlan, 2019)
In the learning process, multimedia has not yet been used much. Interesting multimedia is required to enhance the learning process. Teachers need additional multimedia to assist them in delivering trigonometry teaching materials. This study aims to develop interactive learning media on trigonometry subjects for grade X. Besides; this study is also aimed at knowing the multimedia properness in terms of material and media and the student's responses to multimedia. This study belongs to developmental research employing the ADDIE model that consists of five stages: analysis, design, development, implementation, and evaluation. The study's subject includes students of State Senior High School (SMA Negeri) 1 Imogiri and Senior High School (SMA) Muhammadiyah Imogiri. The data used in this study are qualitative and quantitative, which were collected through observation, interview, and instrument. The assessment result from the material expert is 88.33 and categorized as excellent. The media expert's score is 85.33 and categorized as excellent, and the score of the students is 83.48 and categorized as excellent (based on trial). Thus, it can be concluded that developing interactive learning media on trigonometry subjects for grade X is appropriate to use in the learning process.